Reactive Power: from the optimal dispatch to electrical rates - PART B - Gómez-Ramírez, Gustavo Adolfo (2019)
Nowadays, electricity systems have grown from offering basic electricity services to giving highest quality standards facilities. Today customers have an added value, in Costa Rica ́s case, they are regulated by ARESEP. This institution supervises parameters of quality, service and prices, it is therefore necessary a control and regulation of frequency-voltage variables. This investigation proposes a new rate model from its own research begun part-A that is used as a reference. Looking for electricity’s cost decrease, a linear optimization is the solution to carry out an economic dispatch of the reactive power and through the correct mechanisms, customers will take advantage of a segregated rate.